Cerebral Arterial Air Embolism Associated with Mechanical Ventilation and Deep Tracheal Aspiration. (1st August 2012) - Gursoy, S.; Duger, C.; Kaygusuz, K.; Ozdemir Kol, I.; Gurelik, B.; Mimaroglu, C.
Abstract : Arterial air embolism associated with pulmonary barotrauma has been considered a rare but a well-known complication of mechanical ventilation. A 65-year-old man, who had subarachnoid hemorrhage with Glasgow coma scale of 8, was admitted to intensive care unit and ventilated with the help of mechanical ventilator. Due to the excessive secretions, deep tracheal aspirations were made frequently. GCS decreased from 8–10 to 4-5, and the patient was reevaluated with cranial CT scan. In CT scan, air embolism was detected in the cerebral arteries. The patient deteriorated and spontaneous respiratory activity lost just after the CT investigation. Thirty minutes later cardiac arrest appeared. Despite the resuscitation, the patient died. We suggest that pneumonia and frequent tracheal aspirations are predisposing factors for cerebral vascular air embolism.